Perancangan Promosi Wisata Negeri Atas Angin Berbasis Videografi Sebagai Upaya Pengenalan Pariwisata kabupaten Bojonegoro - Siswanto, Edwind Adryan; Martono, Siswo; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Bojonegoro Regency is one of regencies in East Java province which is geographically quite unique. This diversity raises exotic nature so that it can be used as a tourist attraction.Therefore, as the introduction of tourism in Bojonegoro, East Java as well as to promote the tourism sector in Bojonegoro, the authors put it in the form of design-based tourism promotion hills videografi.Penelitian uses qualitative methods with data collection technique using observation, interviews, literature, existing studies, and studies competitors. The concept used in the design is the "Discover". That is the concept of "Discover" presented to provide information to the target audience that travel the hills of Bojonegoro, East Java has the beauty and uniqueness of each foothill. The concept will be applied to any design which includes video and supporting media. of video creation and media promotion of travel these hills are as efforts to introduce tourism in Bojonegoro, East Java to attract tourists to visit. Besides promoting tourism hills can be enjoyed in various. Kata Kunci : Design, Video, Tourism, hills, Bojonegoro, Discover.